Zmiany w układzie stomatognatycznym u osób starszych w aspekcie gerontologopedii (Conversatoria Linguistica, 2019)
This article lists and briefly describe sage related changes in the stomatognathicsystem. And that established understanding, may become a serious support to the work of elderlypeople’s therapists. The changed to the stomatognathic system affect both general healthcondition, chewing, swallowing, speaking abilities, as well as wellbeing and self esteem of seniors.Moreover, at present, the knowledge on stomatognathic in elderly is fairly underestimatedby doctors and other experts. The significant lack of developed logopaedic thesis on this aspectalso brings in more unawareness.